Litterfall production and its association with environmental conditions in temperate forests of the Sierra Norte de Oaxaca, Mexico - Gutiérrez, Erick; Flores-Galicia, Nihaib; Trejo, Irma (BOSQUE, 2024)
The litterfall that accumulates in the soil is considered as the main source of organic matter, for this reason, it is essential to elucidate the patterns of litterfall production in each region and especially with which factors it is related. The main objective of the present study was to determine the contribution of litterfall to the soil of conifers and oaks and its association with environmental, biological, and disturbance conditions in temperate forests in the highlands part of the Sierra Norte de Oaxaca, Mexico. We established sampling sites along the 1.950 to 3.250 m altitudinal gradient. At each sampling site, we sampled vegetation, collected leaf litter, and measured environmental, biological, and disturbance variables. The forests in the study area have higher litterfall production values than those reported for other world forests (mixed forest: 7,06 mg ha-1 year-1, oak forest: 6,33 mg ha-1 year-1, and coniferous forest: 4,03 mg ha-1 year-1). Litterfall production was related to environmental conditions, with a more significant influence on oaks (temperature and precipitation intensity). In contrast, for conifers, the intensity of disturbance (number of stumps) was the most relevant variable. Conifers presented a greater contribution of litterfall to the soil, registering production peaks at certain times of the year, while the oak trees in the study area did not present litterfall production during the rainy season.